THE EFFECT OF PREGNANT BEHAVIOR ON THE KNOWLEDGE OF BREAST CARE IN PUSKESMAS JOGONALAN I KLATEN - Siti Nurjanah; R. Taufiq Nur Muftiyanto; Aminatul Fatayati (STIKES DUTAGAMA KLATEN, 2017)
Background: Breast care during pregnancy is an important part of the mother's care as preparation for breastfeeding. If during pregnancy the mother does not perform breast care and breast care is only done after delivery will cause some problems such as breast milk does not come out, nipples sometimes not prominent, milk production a little. Nipple not menonjl cause baby difficult to suck, milk production little or not smooth so not enough to meet baby needs. Objective: To know the influence of pregnant woman's behavior on knowledge of breast care I Puskesmas Jogonalan I Klaten. Research Method: using quantitative descriptive research method. The population in this study were all pregnant women from the first trimester to the third trimester who checked in the KIA Polyclinic Puskesmas Jogonalan I Klaten. The sampling technique was simple random sampling with the number of samples of 44 respondents. The instruments in this study were closed questionnaires. Result: There is an influence of education to knowledge of breast care at Puskesmas Jogonalan I Klaten with p value <0,05 (0,010 <0,05), there is no effect of job to knowledge of breast care at Puskesmas Jogonalan I Klaten with p value> 0, 05 (0,465> 0,05), there is influence of earnings to knowledge of breast care at puskesmas Jogonalan I Klaten with p value <0,05 (0,031 <0,05). Conclusion: There is influence of pregnant woman's behavior toward knowledge of breast care at Puskesmas Jogonalan I Klaten.